Impaired social facilitation on voluntary exercise of BALB/cCrSlc mice, a proposed as an autism spectrum disorder model. (February 2021) - Yoshizaki, Kaichi; Asai, Masato; Nakayama, Atsuo
Highlights: A novel breeding home cage for social facilitation and observational learning. Increased voluntary exercise of C57BL/6 J mice in the presence of observer mice. Not increased voluntary exercise of BALB/cCrSlc mice in the presence of observer mice. Not increased voluntary exercise due to observation experience. Abstract: Impaired social facilitation was reported in autism spectrum disorder (ASD) children. However, behavioral analysis methods of social facilitation for ASD model have not been reported. We developed a novel breeding home cage for social facilitation. Voluntary exercise of more social C57BL/6 J mice was significantly increased in the presence of observer mouse compared to that in the absence of observer mouse. In contrast, the presence of observer mouse did not affect voluntary exercise of less social BALB/cCrSlc mice. These suggest that BALB/cCrSlc mice, a mouse model of ASD, exhibited impaired social facilitation. Our method would provide novel clues for ASD pathophysiology.